Experiments on exactly computing non-linear energy transfer rate in MASNUM-WAM - 江兴杰 王道龙 高大鲁 张婷婷 (Chinese journal of oceanology and limnology, 2016)
The Webb-Resio-Tracy（WRT） method for exact computation of the non-linear energy transfer rate was implemented in MASNUM-WAM, which is a third-generation wave model solving the discrete spectral balance equation. In this paper, we describe the transformation of the spectral space in the original WRT method. Four numerical procedures were developed in which the acceleration techniques in the original WRT method, such as geometric scaling, pre-calculating, and grid-searching, are all reorganized. A series of numerical experiments including two simulations based on real data were performed. The availability of such implementation in both serial and parallel versions of the wave model was proved, and a comparison of computation times showed that some of the developed procedures provided good effi cacy. With exact computation of non-linear energy transfer, MASNUM-WAM now can be used to perform numerical experiments for research purposes, which augurs well for further developments of the model.